(untitled) (American Journal of Islam and Society, 2003)
This is a superb book. With penetrating insight and an eloquent style, alDa’mi explores the crucial role that Arabo-lslamic history played in the arguments of such prominent British and American "men of letters" as Thomas Carlyle and Washington Irving. The book opens with a preface, in which he lays out his rationale and purpose, and contains seven chapters, in which he develops his argument. AI-Da’mi seeks to deepen our understanding of nineteenth-century Oriental ism by exploring the works of leading intellectual writers of that time: not the professional historians, but the "men ofletters" who used history to expound their arguments, but with a kind of literary licence not available to a proper historian. His main argument is that the writers used Arabo-Islamic history not simply as an exotic or a romantic flourish, but rather as an integral and important aspect of their discourses to comment upon their own time. For example, Carlyle praises the Prophet as a heroic leader, as a way to warn the British of the dangers of utilitarianism and materialism; Ralph Waldo Emerson likewise does this to send a message to the young American nation; Cardinal John H. Newman to alert Europe to the Ottoman threat; and so on. Al-Da’mi convincingly points out that we can neither understand these writers nor the age itself adequately without properly comprehending this aspect of their writings. This is an important rectification to traditional western scholarship, which typically leaves out all mention of anything non-European in its study of its own intellectual history. (Walter E. Houghton’s classic work on the Victorian age, The Victorian Frame of Mind, 1830-1870, has in its index only one entry for Prophet Muhammad ...